Effect of Defoliation Management and Manuring on Dry Matter Yields and Quality in Sehima Nervosum, Cenchrus Ciliaris and Cenchrus setigerus - Shankarnarayan, K A; Dabadghao, P M; Kumar, Ravi; Rai, P (Annals of Arid Zone, 2016)
Studies to determine the effect of defoliation intervals (10, 2, 30 and 60 days), cutting height (5, 10 and I5 cm) and three nitrogen levels (0, 30 and 60 kg N/ha) on dry matter yields and quality in three range grasses showed that sixty days cutting interval gave highest dry matter yield in Sehima nervosum followed by Cenchrus ciliaris and C.setigerus. Clipping at 15 cm height gave maximum forage yield in S. nervosum followed by C.setigerus and C.ciliaris and appears to be a safe degree of utilization. C.ciliaris and C setigerus showed a significant response to 30 Kg N/ha only, but S.nervosum did not show significant response to any level of nitrogen application. The crude protein content was maximum in C.setigerus at different cutting intervals followed by C.ciliaris and S. nervosum. Nitrogen enhanced the crude protein in all the three grasses. Maximum underground biomass production was observed in C. setigerus at 60 days cutting interval. This trend was discernible at lower intervals in C.ciliaris and S. nervosum. C.setigerus alone showed consistent increase in underground biomass production and carbohydrate content to different cutting heights and cutting intervals. Carbohydrate increased with different nitrogen levels in C. ciliaris only.